High juvenile mortality during migration in a declining population of a long‐distance migratory raptor. (4th April 2015) - Oppel, Steffen; Dobrev, Vladimir; Arkumarev, Volen; Saravia, Victoria; Bounas, Anastasios; Kret, Elzbieta; Velevski, Metodija; Stoychev, Stoycho; Nikolov, Stoyan C.; Arroyo, Beatriz
<x xml:space="preserve">Abstract</x> Many populations of long‐distance migrants are declining and there is increasing evidence that declines may be caused by factors operating outside the breeding season. Among the four vulture species breeding in the western Palaearctic, the species showing the steepest population decline, the Egyptian Vulture Neophron percnopterus, is a long‐distance migrant wintering in Africa. However, the flyways and wintering areas of the species are only known for some populations, and without knowledge of where mortality occurs, effective conservation management is not possible. We tracked 19 juvenile Egyptian Vultures from the declining breeding population on the Balkan Peninsula between 2010 and 2014 to estimate survival and identify important migratory routes and wintering areas for this species. Mortality during the first autumn migration was high (monthly survival probability 0.75) but mortality during migration was exclusively associated with suboptimal navigation. All birds from western breeding areas and three birds from central and eastern breeding areas attempted to fly south over the Mediterranean Sea, but only one in 10 birds survived this route, probably due to stronger tailwind. All eight birds using the migratory route via Turkey and the Middle East successfully completed their first autumn migration. Of 14 individual and environmental variables examined to explain why juvenile birds did or did not successfully complete their first migration, the natal origin of the bird was the most influential. We speculate that in a declining population with fewer experienced adults, an increasing proportion of juvenile birds are forced to migrate without conspecific guidance, leading to high mortality as a consequence of following sub‐optimal migratory routes. Juvenile Egyptian Vultures wintered across a vast range of the Sahel and eastern Africa, and had large movement ranges with core use areas at intermediate elevations in savannah, cropland or desert. Two birds were shot in Africa, where several significant threats exist for vultures at continental scales. Given the broad distribution of the birds and threats, effective conservation in Africa will be challenging and will require long‐term investment. We recommend that in the short term, more efficient conservation could target narrow migration corridors in southern Turkey and the Middle East, and known congregation sites in African wintering areas.